The lowland : a novel - Lahiri, Jhumpa (Alfred A. Knopf, 2013)
Brothers Subhash and Udayan Mitra pursue vastly different lives--Udayan in rebellion-torn Calcutta, Subhash in a quiet corner of America--until a shattering tragedy compels Subhash to return to India, where he endeavors to heal family wounds.